Preserving Ceramic Heritage Values Through Sustainable Design - Olalere , Folasayo Enoch; Shuaib, Ab. Aziz (2014)
In recent time, the conservative approach of preserving ceramic heritage wares is facing complex problems. Due to its fragility, mechanical damage causes irreversible deterioration such as breaks, surface abrasion, cracks, and sometimes completes fragmentation of the body. Thus, sustainable approach is seen as a possible and potential alternative for preserving ceramic heritage values. Sustainable concept involves transforming heritage values into commodities that have significant contemporary values. Hence, this study seeks to explore the viability of sustainable development concept in preserving ceramic heritage values. Using Kelantan traditional ceramics as a case study, the paper identifies the unique heritage values (aesthetic qualities) that can be sustained as genius loci. This was achieved by analysing the decorative motifs on heritage wares using Golden section; after which the unique elements were integrated into contemporary ceramic products. The products were evaluation and the result shows that; applying this approach in ceramics will not only sustain the heritage values, but also enhance contemporary products.